A Randomized Controlled Trial Comparing Two Self‐Administered Educational Strategies for Patients With Knee Osteoarthritis. Issue 3 (16th February 2021) - Lopez‐Olivo, Maria A.; des Bordes, Jude K.; Lin, Heather; Volk, Robert J.; Rizvi, Tara; Suarez‐Almazor, Maria E.
Abstract : Objective: The objective of this study was to assess the efficacy of self‐administered patient educational tools in improving knowledge and behaviors for the management of knee osteoarthritis. Methods: We conducted a randomized clinical trial in patients with knee osteoarthritis to assess the efficacy of providing a video for entertainment education, in combination with two booklets, compared with providing the booklets alone. We evaluated changes in scores on a patient knowledge questionnaire, the Decisional Conflict Scale, the Arthritis Self‐Efficacy Scale, and the Effective Consumer Scale between baseline and same day, 3 months, and 6 months post intervention. We used linear regression models to explore associations between demographic characteristics and outcomes, testing for interactions. Results: Two hundred nineteen participants were randomly assigned to receive the video + booklets (n = 109) or the booklets alone (n = 110). The mean age of participants was 64.6 (±8.3) years. At 6 months, statistically significant improvements were observed in knowledge and decisional conflict scores for both groups, and statistically significant improvements in the behavior to participate in their health care were observed in the video + booklets group. The video + booklets group was more knowledgeable immediately post intervention than the booklet group (mean difference 0.39 [95% confidence interval 0.02‐0.76]). No other significant changes in outcomes were observed at 6 months between the two groups. The video + booklets combination was associated with decreased decisional conflict in Spanish speakers and increased self‐efficacy in those with less than a high school education. Conclusion: Although both education strategies were associated with improved knowledge and reduced decisional conflict at 6 months, receiving the video + booklets in combination, compared with receiving the booklets alone, proved to be more effective in changing behaviors and appeared to have some advantages for Spanish speakers and those who were less educated.